Flexible low-temperature-resistant fire-resistant fireproof cable and preparation method thereof

By using a composite material of PEEK insulating sheath layer and carbon fiber and polyethersulfone porous fibers in the fire-proof cable, combined with braided copper mesh metal shielding protection layer and thermally insulated fire-proof layer, the increased hardness and stress cracking of the fire-proof cable at low temperatures is solved. Problem, higher mechanical strength and crack resistance are achieved.

CN119170333APending Publication Date: 2024-12-20FUJIAN QUANZHOU YANGFAN WIRE & CABLE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411202299.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing fire-proof cables have increased hardness in low-temperature environments, which are difficult to bend, and are prone to stress cracking for a long time, which poses safety hazards.

Method used

It adopts PEEK insulating sheath layer, braided copper mesh metal shielding protective layer, polyimide outer insulation layer and thermal fireproof layer, and combines a composite material of carbon fiber and polyethersulfone porous fiber to enhance the mechanical strength and tensile resistance of the cable. Improve low temperature brittleness.

Benefits of technology

It extends the service life of the cable, improves the bending and crack resistance at low temperatures, reduces the risk of embrittlement, and ensures the reliability and safety of the cable in low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170333A_ABST
    Figure CN119170333A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fireproof cables, and particularly discloses a flexible low-temperature-resistant fireproof cable and a preparation method thereof. A flexible low-temperature-resistant fire-resistant fireproof cable comprises at least one cable core containing a conductor, the outer surface of the cable core is sequentially coated with a fire-resistant heat insulation layer, a braided copper net metal shielding protection layer, a polyimide outer insulation layer and a PEEK insulation sheath layer, and the space between the fire-resistant heat insulation layer and the cable core is filled with a heat insulation fireproof layer. The PEEK insulating sheath layer is formed by extruding a PEEK insulating sheath material, and the PEEK insulating sheath material is prepared from the following raw materials in parts by weight: 2.5 to 4.5 parts of PEEK, 1 to 2 parts of TPEE, 0.5 to 1.5 parts of carbon fiber, 0.1 to 0.15 part of phenylacetylene polyimide and 0.5 to 1.5 parts of polyether sulfone porous fiber. The flexible low-temperature-resistant fire-resistant fireproof cable has the advantages of being small in bending radius, high in flexibility, resistant to distortion and not prone to embrittlement and cracking at the low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fireproof cables, and more specifically, to a flexible low-temperature-resistant and fire-resistant fireproof cable and a preparation method thereof. Background Art

[0002] According to statistics, fires caused by electrical reasons account for about 50% of fires in my country. When a fire occurs, the flames may ignite the insulation and sheath materials in traditional wires and cables, thereby generating a large amount of smoke and toxic and harmful gases, which will lead to the further expansion of the fire accident. Especially in places such as underground rail transit stations where the space is small, the population is dense, and the humidity is high, once a fire accident occurs, a large amount of smoke and toxic and harmful gases will be more difficult to disperse. If the power supply safety of fire cables such as the control lines of fire-fighting equipment, the signal transmission lines of the automatic fire alarm system, the fire broadcast lines and the fire telephone lines cannot be guaranteed, and the correct fire-fighting and evacuation mode is started, it is easy to cause greater loss of life and property. Therefore, the reliability of fire-proof cables is crucial.

[0003] The fireproof materials commonly used in the market at present use polyolefin or POE as the base material, or use silicone rubber as the base material, and design the mineral material formula to make ceramic polyolefin or ceramic silicone rubber. The Chinese invention patent document with application number CN2016106676924 discloses a ceramic silicone rubber insulated heat-resistant fireproof cable, including a cable core and a ceramic silicone rubber insulating sheath; the raw materials of the ceramic silicone rubber insulating sheath include by weight: 30-50 parts of ceramic silicone rubber, 50-70 parts of EPDM rubber, 10-20 parts of modified lignin, 10-20 parts of sintered red mud, 15-22 parts of fly ash, and glass fiber reinforced plastic. 8-16 parts of glass microspheres, 0.8-1.5 parts of zinc oxide, 0.4-1 parts of cyclohexanone peroxide, 0.3-0.9 parts of tert-butyl perbenzoate, 0.8-1.2 parts of tert-butylphenol formaldehyde resin, 1.5-2.5 parts of diisopropylbenzene peroxide, 1.5-3 parts of triethyl citrate, 1.5-2.5 parts of dioctyl terephthalate, 2-3 parts of epoxidized soybean oil, 0.5-1.5 parts of tricresyl phosphate, 1.5-3.5 parts of antioxidant NBC, and 1-2.5 parts of antioxidant AW.

[0004] The fireproof cable has insulation and electrical properties, is relatively soft at room temperature, and is easy to bend and lay. However, the fireproof cable becomes harder in a low temperature environment below -30℃, making it difficult to bend, unable to withstand multiple movements or bends, and inconvenient to lay. It may also cause stress cracking when used at low temperatures for a long time, posing a safety hazard. Summary of the invention

[0005] In order to make the fire-resistant cable have better bendability and flexibility at low temperatures and not easily produce stress cracking during long-term use at low temperatures, the present application provides a flexible low-temperature resistant and fire-resistant cable and a preparation method thereof.

[0006] In the first aspect, the present application provides a flexible low temperature resistant, fire resistant and fireproof cable, which adopts the following technical solution: A flexible low-temperature-resistant, fire-resistant and fire-proof cable comprises at least one cable core containing a conductor, wherein the outer surface of the cable core is sequentially coated with a fire-resistant insulation layer, a braided copper mesh metal shielding protective layer, a polyimide outer insulation layer and a PEEK insulation sheath layer, a heat-insulating and fire-proof layer is filled between the fire-resistant insulation layer and the cable core, and the PEEK insulation sheath layer is formed by extruding a PEEK insulation sheath material, wherein the PEEK insulation sheath material comprises the following raw materials in parts by weight: 2.5-4.5 parts of PEEK, 1-2 parts of TPEE, 0.5-1.5 parts of carbon fiber, 0.1-0.15 parts of phenylethynyl polyimide, and 0.5-1.5 parts of polyethersulfone porous fiber.

[0007] By adopting the above technical scheme, a fire-resistant insulation layer and a heat-insulating fireproof layer are used to increase the flame retardant and fireproof energy of the cable. The woven copper mesh metal shielding protective layer is mainly used to ground the current of the interference signal, thereby effectively preventing the external electromagnetic field from interfering with the internal signal line of the cable. At the same time, it can also prevent the escape of the transmission signal, reduce the loss of the transmission signal, improve the transmission efficiency, and improve the stability and reliability of the cable transmission signal. It can also increase the mechanical strength of the cable, improve the tensile resistance, and extend the service life. The polyimide outer insulation layer provides insulation protection for the internal conductor, and the PEEK insulation sheath layer has excellent mechanical properties, high tensile strength and tolerance The ability to bend repeatedly for a long time, and can withstand high-intensity stress impact; PEEK (polyetheretherketone) is an aromatic crystalline thermoplastic polymer material with a high melting point, high mechanical strength, high temperature resistance, impact resistance, flame retardancy, acid and alkali resistance, hydrolysis resistance, wear resistance, fatigue resistance, radiation resistance and good electrical properties. Thermoplastic elastomer (TPEE) is a block copolymer containing polyester hard segment and polyether soft segment, in which the polyether soft segment and the uncrystallized polyester form an amorphous phase. The polyester hard segment partially crystallizes to form a crystalline micro-region. The physical cross-linking effect gives the soft segment elasticity, making TPEE softer, and the plasticizing temperature is low, the strength is high, the creep resistance is good, and the resilience is excellent. It has good impact resistance, bending fatigue resistance, wear resistance, and dimensional stability. TPEE and PEEK have good compatibility and are blended in a special ratio to improve the polarity and hydrophilicity of PEEK, reduce the hardness and plasticizing temperature of PEEK, thereby increasing the force and the mechanical, thermal and tribological properties of the composite material, and obtaining an excellent composite material, so that the PEEK insulating sheath layer has high strength, high wear resistance, oil resistance, and excellent insulation properties. It also has the characteristics of low smoke, halogen-free, and flame retardant. Phenylacetylene polyimide contains phenylacetylene structure, which can be cross-linked, thereby firmly locked on the surface of carbon fiber and polyethersulfone porous fiber, thereby making up for the carbon fiber and polyether The weaker bonding between sulfone porous fiber and PEEK improves the interface bonding environment between PEEK and fiber, improves the interface bonding ability between the two, and can make carbon fiber and polyethersulfone porous fiber more evenly distributed in the resin matrix. The bonding between carbon fiber and PEEK is relatively good, the area of ​​PEEK adhesion on the fiber is larger, and the fiber surface becomes rough, the fiber surface at the break is scaly, the grooves at the junction of the fiber and PEEK are reduced, and the PEEK matrix embeds the fiber more tightly, thereby increasing the mechanical properties, improving the tensile strength and impact properties, and improving the bending strength, thereby weakening the low-temperature embrittlement and improving the service life in a low-temperature environment.

[0008] Optionally, the preparation method of the PEE insulating sheath material is as follows: The phenylethynyl polyimide is dissolved to obtain an impregnation solution, the carbon fiber and the polyethersulfone porous fiber are immersed in the impregnation solution for 2-3 hours at room temperature, taken out and dried to obtain the pretreated fiber; The pretreated fibers are mixed evenly with a dispersant and deionized water, filtered, sprayed with a water-based epoxy adhesive, and dried to form a gauze; PEEK and TPEE are mixed and melted to obtain a melt, which is then cast into a mold multiple times, and a gauze is laid on the cast melt between each two times. Finally, the PEEK insulating sheath material is obtained by pressing at a pressure of 0.8-1.2 MPa for 20-30 seconds and crushing.

[0009] By adopting the above technical scheme, phenylethynyl polyimide can be deposited on the surface of carbon fiber and polyethersulfone porous fiber by impregnation, and after being dispersed by dispersant and deionized water, it is filtered to form a fiber skeleton, and then sprayed with water-based epoxy adhesive to bond the carbon fiber and polyethersulfone porous fiber into a more stable skeleton structure; TPEE and PEEK are mixed to obtain a melt, and then the melt and the gauze skeleton are alternately arranged to form an interlayer structure. When cracks occur and expand in the PEEK sheath material, the gauze is pulled off, one end is embedded in the sheath layer, and a small plastic deformation occurs at the other end. Therefore, during the expansion of the interlayer cracks, Nanoscale bridging occurs in the gauze in the sheath layer, further consuming energy. At the same time, carbon fiber and polyethersulfone porous fibers themselves have good toughness. During the crack propagation process, carbon fiber and polyethersulfone porous fibers can not only deflect and terminate the cracks, but also absorb additional energy through their own elastic deformation. In addition, carbon fiber and polyethersulfone porous fibers are prone to longitudinal tearing damage, further absorbing energy, improving interlayer fracture toughness, and significantly improving crack resistance and tensile resistance, thereby improving the impact crack resistance and low-temperature brittleness of the sheath layer, and further enhancing the low-temperature resistance and service life of the current surface.

[0010] Optionally, the preparation method of the polyethersulfone porous fiber is as follows: The cellulose nanocrystals are added to deionized water to prepare a suspension with a concentration of 1-2 wt%, methyltrimethoxysilane is added, the mixture is stirred at room temperature for 3-4 hours, red mud is added, ultrasonic dispersion is performed for 15-20 minutes, and the mixture is freeze-dried and then crushed to obtain a porous material powder, wherein the mass ratio of the cellulose nanocrystals, methyltrimethoxysilane and red mud is 1:0.8-1:1-2; The polyethersulfone is dried and dissolved to prepare a solution with a concentration of 28-30wt%, the porous material powder is added, ultrasonic dispersion is performed for 20-30min, the solution is filtered with a 200-mesh sieve, and the solution is allowed to stand for 10-12h for degassing to obtain a spinning solution, and wet spinning is performed to obtain polyethersulfone porous fibers. The mass ratio of the porous material powder to the polyethersulfone is 1.8-2.4:100.

[0011] By adopting the above technical scheme, the high crystallinity, high rigidity, special surface chemical properties and biological characteristics of cellulose nanocrystals are modified by surface silanization of methyltrimethoxysilane, and part of the hydrophilic hydroxyl groups on their surface are converted into hydrophobic methylsiloxane. Red mud is a large amount of inorganic waste generated in the production process of alumina by the Bayer process. Its main components are oxides and hydroxides of aluminum, iron, silicon and titanium. After the two are mixed, the porous material obtained by freeze-drying has high porosity and ultra-low density, presents a network structure, and has interconnected pores, indicating that the introduction of red mud can maintain the porous microstructure of the nanocellulose-based skeleton; the inorganic component red mud is evenly dispersed in the porous material powder, and as a thermally stable phase of the porous material, it provides thermal insulation protection during the combustion process, effectively improving The flame retardancy of the porous material powder can protect the skeleton of the porous material powder. The porous material powder is added to the polyethersulfone solution, which has a certain effect on the phase separation of polyethersulfone. The size of the polyethersulfone microspheres formed by the phase separation is reduced, which inhibits the deflection of microcracks and hinders the propagation path of the cracks, which is conducive to consuming more energy, improving the interlaminar fracture toughness, and improving the crack resistance at low temperatures. Moreover, the porous material is distributed between the melt in the polyethersulfone porous fiber. It can not only anchor the cracks, but also play a bridging role. When the cracks expand, the porous material pulls out and breaks, consuming a lot of energy. The superposition of the two mechanisms significantly improves the toughness of the PEEK sheath material and improves the crack resistance at low temperatures.

[0012] Optionally, each cable core includes, from the inside to the outside, a plurality of conductors twisted together, a polytetrafluoroethylene insulation layer wrapped around the conductor, an insulation reinforcement layer extruded outside the polytetrafluoroethylene insulation layer, and a filling layer filled between the conductor and the polytetrafluoroethylene insulation layer.

[0013] By adopting the above technical solution, the polytetrafluoroethylene insulation layer wrapped on multiple conductors has a very low dielectric constant and is an ideal insulating material. Its unique porous structure can minimize the dielectric constant of the insulation and minimize the loss and distortion of the signal during transmission in the cable. The cable has a smaller attenuation constant and has certain thermal stability and mechanical flexibility. The low-temperature performance of polytetrafluoroethylene is good, which can avoid the disadvantages of heavy cable weight and poor bending performance caused by the use of mineral insulation layers, so that the temperature relative stability and flexibility of the cable are better than those of solid cables.

[0014] Optionally, the filling layer is formed by mechanically twisting and weaving glass fiber ropes and ceramic silicone strips.

[0015] By adopting the above technical solution, the material is soft at room temperature, shock-absorbing and impact-resistant, and has good shell thermal insulation; a hard shell is formed at a temperature above 550°C, does not fall off after sintering, has a weight loss of less than 28%, and the formed ceramic body does not shrink.

[0016] Optionally, the polytetrafluoroethylene insulation layer is a polytetrafluoroethylene microporous membrane.

[0017] By adopting the above technical scheme, the polytetrafluoroethylene microporous membrane has excellent resistance to low temperature cracking. In a low temperature environment, it can maintain its flexibility and elasticity and is not prone to brittleness or cracking. Moreover, it has a porous structure, a large longitudinal stretching multiple, and high tensile strength, which can improve the flexibility and bending resistance of the cable.

[0018] Optionally, the insulation reinforcement layer is a radiation cross-linked polyolefin cable material.

[0019] By adopting the above technical scheme, the radiation cross-linked polyolefin cable material has excellent insulation properties, can withstand high voltage without breakdown, ensure the safe operation of the cable, and has high heat deformation temperature and thermal stability, can maintain temperature insulation in high temperature environment, is not easy to age, has good chemical corrosion resistance, tensile strength, does not contain halogen, and does not produce toxic gases when burned.

[0020] Optionally, the heat-insulating and fire-proof layer is a polyolefin material containing a flame retardant.

[0021] By adopting the above technical solution, polyolefin material is a kind of high molecular compound formed by the polymerization of olefin monomers, which has excellent heat resistance, electrical insulation and chemical stability, good thermal insulation and fire resistance, can effectively prevent the spread of flames, and can keep the cable working normally for a certain period of time, thereby ensuring the stable transmission of electricity and signals, and has good processing performance and environmental stress cracking resistance, which is convenient for the production and installation of cables.

[0022] Optionally, the fire-resistant insulation layer is a mica tape impregnated with an impregnation liquid containing a flame retardant by vacuum pressure impregnation.

[0023] By adopting the above technical scheme, the mica tape has a very good fire resistance time and good electrical insulation, can prevent current leakage and electrical failure, and maintains stable physical and chemical properties in a high temperature environment, and will not melt, drip or the like. It can continue to have a fire-resistant and heat-insulating effect in a high temperature environment such as a fire, and has high tensile strength and tear strength, can withstand various mechanical stresses generated by the cable during use, and ensure the integrity and service life of the cable. In addition, it is an inorganic non-metallic material, does not contain harmful substances, and is relatively environmentally friendly. Through vacuum pressure impregnation treatment, the impregnation liquid containing the flame retardant is evenly distributed on the surface of the mica tape, forming a flame retardant layer without air gaps and good integrity, thereby improving the flame retardant ability of the mica tape.

[0024] Optionally, the flame retardant is prepared as follows: Disperse the carbon microspheres in anhydrous ethanol, add ammonia water until the pH value is ≥12, heat to 40-45°C, add magnesium chloride solution until the pH value is 10, stir at constant temperature for 1-2h, filter, wash, dry and grind to obtain material A; Mix lauric acid and tetradic acid at a molar ratio of 6:4 at 70-80°C to obtain a phase change material, add nano-silicon dioxide and carbon black, stir for 1-2 hours, and vacuum dry to obtain material B, wherein the mass ratio of the phase change material, nano-silicon dioxide and carbon black is 1:0.6-0.8:0.16-0.18; The material A and the material B are uniformly mixed in a mass ratio of 1:0.4-0.6 to prepare a flame retardant.

[0025] By adopting the above technical scheme, the carbon microspheres have a large specific surface area and can migrate to the surface of the polyolefin material or the mica tape. The free radicals on the surface of the carbon microspheres can couple with the macromolecular free radicals generated by the degradation of the polyolefin or the macromolecular free radicals generated by the degradation of the components in the impregnation solution to form crosslinks, thereby inhibiting the breakage of the molecular chain and isolating the heat, thereby improving the thermal stability and flame retardancy. Moreover, the carbon microspheres can capture highly active HO free radicals to inhibit the combustion degradation reaction of the material, and form an effective carbon layer to isolate heat transfer and play a flame retardant role. Magnesium hydroxide can improve the smoke phenomenon of the carbon microspheres. By using magnesium hydroxide to coat the carbon microspheres, the self-agglomeration of the carbon microspheres in the impregnation solution is improved. Moreover, the thermal stability of magnesium hydroxide is higher than that of the carbon microspheres. Magnesium hydroxide is used as the shell layer and the carbon microspheres as The core can improve the thermal stability of the flame retardant. The decomposition of magnesium hydroxide can absorb heat on the one hand, and release water vapor to dilute the oxygen concentration on the other hand. Therefore, it has good self-extinguishing properties and improved droplet phenomenon. The effective carbon layer formed during the combustion process isolates the combustible gas from diffusing outward and cuts off the combustion reaction. Lauric acid and tetradecanoic acid are fatty acids, which are a typical organic phase change material with the advantages of high latent heat and no corrosion. Nano-silica is used as the supporting material. Nano-silica is a porous and loose spherical structure. Carbon black has a multi-layer internal pore structure. The pores and surface of nano-silica can be filled with phase change materials. The layered structure of carbon black can be better combined with the spherical structure of nano-silica to form a more effective heat conduction path, thereby absorbing the heat generated by combustion and achieving a flame retardant effect.

[0026] In a second aspect, the present application provides a method for preparing a flexible low-temperature resistant, fire-resistant and fireproof cable, using the following technical solution: A method for preparing a flexible low-temperature-resistant, fire-resistant and fireproof cable comprises the following steps:.

[0027] A plurality of conductors are twisted together, and then glass fiber ropes and ceramic silicone strips are twisted and braided on the twisted plurality of conductors to form a filling layer, a polytetrafluoroethylene microporous membrane is wrapped outside the filling layer to form a polytetrafluoroethylene insulation layer, and then a radiation cross-linked polyolefin cable material is extruded on the surface to obtain an insulation reinforcement layer, that is, a cable core; A polyolefin material containing a flame retardant is extruded on the outside of at least one cable core to obtain a heat-insulating and fire-proof layer, which is then wrapped with a mica tape that has been vacuum-pressure-impregnated with an impregnation solution containing a flame retardant to obtain a fire-resistant and heat-insulating layer, and then a braided copper mesh is wrapped to form a braided copper mesh metal shielding protective layer, followed by a polyimide film to form a polyimide outer insulating layer, and finally a PEEK insulating sheath layer is extruded on the polyimide outer insulating layer.

[0028] In summary, this application has the following beneficial effects: 1. Since the present application covers the cable core with a heat-insulating fireproof layer, a fire-resistant insulation layer, a braided copper mesh metal shielding protective layer, a polyimide outer insulation layer and a PEEK insulation sheath layer, it integrates flame retardancy, heat insulation, fire resistance and fire isolation, so that the cable has good fire resistance and flame retardancy, can prolong the time for heat conduction to the cable core inside the cable, and increase the rescue and escape time at the fire scene. Moreover, the PEEK insulation sheath material is made of raw materials such as PEEK, TPEE, carbon fiber, and polyethersulfone porous fiber. The outer sheath has strong bending strength and crack resistance, is not easy to crack, can reduce the brittleness of the cable in a low temperature environment, improve the low-temperature brittleness temperature, and increase the low-temperature resistance of the cable.

[0029] 2. In the present application, cellulose nanocrystals and red mud pretreated with silane are preferably used to prepare porous material powder, and then the porous material powder is used to carry out wet spinning with a solution of polyethersulfone to prepare polyethersulfone porous fibers, thereby increasing the flame retardancy of the polyethersulfone porous fibers and increasing their crack resistance.

[0030] 3. In this application, a polyolefin material containing a special flame retardant is used as a heat-insulating and fireproof layer, and a mica tape impregnated with a special flame retardant is used as a fire-resistant insulation layer. The flame retardant is made of magnesium hydroxide-coated carbon microspheres as material A, and carbon black and nano-silicon dioxide encapsulated lauric acid mixed with tetradecanoic acid as material B. It can effectively reduce heat transfer, play an isolation box protection role, promote the formation of a carbonized layer, reduce smoke generation, and enhance flame retardancy and smoke suppression effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the structure of the flexible low-temperature-resistant and fire-resistant cable for this application.

[0032] In the figure: 1. Cable core; 11. Conductor; 12. Polytetrafluoroethylene insulation layer; 13. Insulation reinforcement layer; 14. Filling layer; 2. Fire-resistant insulation layer; 3. Braided copper mesh metal shielding protection layer; 4. Polyimide outer insulation layer; 5. PEEK insulation protection sleeve layer; 6. Thermal insulation and fireproof layer. DETAILED DESCRIPTION

[0033] The following examples further illustrate the present application in detail.

[0034] Preparation Example 1-10 of PEEK Insulation Sheath Material Preparation Example 1: 0.15 kg of phenylethynyl polyimide was dissolved in DMAc to obtain an impregnation solution with a concentration of 15 wt%, 1.5 kg of carbon fiber and 1.5 kg of polyethersulfone porous fiber were immersed in the impregnation solution, immersed at room temperature for 3 hours, taken out, and dried at 80°C for 10 hours to obtain pretreated fibers. The polyethersulfone porous fiber was prepared by drying the polyethersulfone at 140°C, dissolving it in NMP (the mass ratio of polyethersulfone to NMP was 2:5) in a 100°C oil bath, filtering it through a 200-mesh sieve, and degassing it for 12 hours to obtain a spinning solution. The spinning was wet-spun using a concentric circular conventional circular spinneret with 50 holes and a pore size of 80 μm. Distilled water was used as a coagulation bath, and double diffusion and water washing were performed in sequence. The pretreated fiber, 0.01 kg dispersant and 5 kg deionized water were mixed evenly and then filtered, and a water-based epoxy adhesive was sprayed on the mixture, and the mixture was dried at 80°C to form a gauze. The dispersant was sodium tripolyphosphate, and the amount of the water-based epoxy adhesive sprayed was 1% of the total weight of the pretreated carbon fiber and the polyethersulfone porous fiber. The water-based epoxy adhesive was selected from Foshan Juntu New Materials, model JT-812; PEEK and TPEE were mixed and melted at 390°C to obtain a melt, which was then cast into a mold in 5 portions, and a gauze was laid on the cast melt between each two portions. Finally, the mixture was pressed at a pressure of 1.2 MPa for 20 seconds and crushed to 10 mm to obtain a PEEK insulating sheath material. TPEE was selected from Suzhou Kaisai Plasticizing, with a brand name of 4556 and a product number of TPEE001. PEEK was selected from Shanghai Heruifeng Plasticizing, produced in Japan Mitsui, with a product number of PL450C. The gauze laid between the two layers of the melt had a thickness of 1 / 10 of that of one layer of the melt.

[0035] Preparation Example 2: 0.1 kg of phenylethynyl polyimide was dissolved in DMAc to obtain an impregnation solution with a concentration of 10 wt%, 0.5 kg of carbon fiber and 0.5 kg of polyethersulfone porous fiber were mixed and immersed in the impregnation solution, immersed at room temperature for 2 hours, taken out, and dried at 80°C for 10 hours to obtain pretreated fibers. The polyethersulfone porous fiber was obtained by drying the polyethersulfone at 140°C, dissolving it in NMP (the mass ratio of polyethersulfone to NMP was 2:5) in a 100°C oil bath, filtering it through a 200-mesh sieve, and degassing it for 12 hours to obtain a spinning solution. The spinning was wet-spun using a concentric circular conventional circular spinneret with 50 holes and a pore size of 80 μm. Distilled water was used as a coagulation bath, and double diffusion and water washing were performed in sequence. The pretreated fiber was mixed with 0.01 kg dispersant and 3 kg deionized water, and then filtered, sprayed with a water-based epoxy adhesive, and dried at 80°C to form a gauze. The dispersant was sodium tripolyphosphate, and the amount of the water-based epoxy adhesive sprayed was 1% of the total weight of the pretreated carbon fiber and the polyethersulfone porous fiber. The water-based epoxy adhesive was selected from Foshan Juntu New Materials, model JT-812; PEEK and TPEE were mixed and melted at 400°C to obtain a melt, which was then poured into a mold in 7 portions, and a gauze was laid on the cast melt between each two portions. Finally, the mixture was pressed at a pressure of 0.8 MPa for 30 seconds and crushed to 10 mm to obtain a PEEK insulating sheath material. TPEE was selected from Suzhou Kaisai Plasticizing, with a brand name of 4556 and a product number of TPEE001. PEEK was selected from Shanghai Heruifeng Plasticizing, produced in Japan Mitsui, with a product number of PL450C. The gauze laid between the two layers of the melt had a thickness of 1 / 4 of the thickness of one layer of the melt.

[0036] Preparation Example 3: The difference from Preparation Example 1 is that the carbon fiber and the polyethersulfone porous fiber are not pretreated with the phenylethynyl polyimide impregnation solution.

[0037] Preparation Example 4: The difference from Preparation Example 1 is that polyethersulfone porous fibers are not added, and the pretreated carbon fibers are added to the dispersant and deionized water, and the remaining operations are the same.

[0038] Preparation Example 5: The difference from Preparation Example 1 is that no carbon fiber is added, and the pretreated polyethersulfone porous fiber is added to the dispersant and deionized water, and the rest of the operations are the same.

[0039] Preparation Example 6: The difference from Preparation Example 1 is that TPEE is not added.

[0040] Preparation Example 7: The difference from Preparation Example 1 is that the polyethersulfone porous fiber is prepared by the following method: 35 g of cellulose nanocrystals were added to deionized water to prepare a suspension with a concentration of 2 wt%, methyltrimethoxysilane was added, the mixture was stirred at room temperature for 4 h, red mud was added, ultrasonic dispersion was performed for 20 min, freeze-dried at -70 °C for 8 h, and then crushed to obtain a porous material powder with a particle size of 30 μm, wherein the mass ratio of cellulose nanocrystals, methyltrimethoxysilane and red mud was 1:1:2; The polyethersulfone was dried at 140°C and dissolved with NMP to prepare a solution with a concentration of 28 wt%, the porous material powder was added, ultrasonic dispersion was carried out for 30 minutes, the solution was filtered with a 200-mesh sieve, and the solution was allowed to stand for 12 hours for degassing to obtain a spinning solution, and wet spinning was performed to obtain polyethersulfone porous fibers. The mass ratio of the porous material powder to the polyethersulfone was 2.4:100.

[0041] Preparation Example 8: The difference from Preparation Example 1 is that the polyethersulfone porous fiber is prepared by the following method: 35 g of cellulose nanocrystals were added to deionized water to prepare a suspension with a concentration of 2 wt%, methyltrimethoxysilane was added, the mixture was stirred at room temperature for 4 h, red mud was added, ultrasonic dispersion was performed for 20 min, freeze-dried at -70 °C for 8 h, and then crushed to obtain a porous material powder with a particle size of 30 μm, wherein the mass ratio of cellulose nanocrystals, methyltrimethoxysilane and red mud was 1:1:2; The polyethersulfone was dried at 140°C and dissolved with NMP to prepare a solution with a concentration of 28 wt%, the porous material powder was added, ultrasonic dispersion was carried out for 30 minutes, the solution was filtered with a 200-mesh sieve, and the solution was allowed to stand for 12 hours for degassing to obtain a spinning solution, and wet spinning was performed to obtain polyethersulfone porous fibers. The mass ratio of the porous material powder to the polyethersulfone was 2.4:100.

[0042] Preparation Example 9: The difference from Preparation Example 7 is that no red mud is added to the porous material powder.

[0043] Preparation Example 10: The difference from Preparation Example 7 is that methyltrimethoxysilane is not added.

[0044] Preparation Examples 11-14 of Flame Retardants Preparation Example 11: Disperse 100 g of carbon microspheres in 1000 mL of anhydrous ethanol, ultrasonically vibrate for 5 min at 20 ° C and 80 kHz, add ammonia water until the pH value is ≥ 12, heat to 40 ° C, add 0.5 mol / L magnesium chloride solution at a rate of 3 mL / min until the pH value is 10, stir at constant temperature for 1 h, filter, wash with anhydrous ethanol and deionized water in turn, then dry at 100 ° C, grind, and obtain material A; Lauric acid and myristic acid were mixed uniformly at a molar ratio of 6:4 at 70°C to obtain a phase change material, nano-silicon dioxide and carbon black were added, stirred for 2 hours, and vacuum dried at 35°C for 48 hours to obtain material B, wherein the mass ratio of the phase change material, nano-silicon dioxide and carbon black was 1:0.6:0.16; The material A and the material B are uniformly mixed in a mass ratio of 1:0.4 to prepare a flame retardant.

[0045] Preparation Example 12: 100 g of carbon microspheres were dispersed in 1000 mL of anhydrous ethanol, ultrasonically vibrated at 20 ° C and 80 kHz for 5 min, ammonia water was added dropwise until the pH value was ≥ 12, the temperature was raised to 45 ° C, and a 0.5 mol / L magnesium chloride solution was added dropwise at a rate of 3 mL / min until the pH value was 10, stirred at constant temperature for 2 h, filtered, washed with anhydrous ethanol and deionized water in turn, and then dried at 100 ° C, ground, and obtained A material; Lauric acid and myristic acid were mixed at a molar ratio of 6:4 at 80°C to obtain a phase change material, nano-silicon dioxide and carbon black were added, stirred for 1 hour, and vacuum dried at 35°C for 48 hours to obtain material B, wherein the mass ratio of the phase change material, nano-silicon dioxide and carbon black was 1:0.8:0.18; The material A and the material B are uniformly mixed in a mass ratio of 1:0.6 to prepare a flame retardant.

[0046] Preparation Example 13: The difference from Preparation Example 1 is that no magnesium chloride is added to material A, and carbon microspheres are used as material A.

[0047] Preparation Example 14: The difference from Preparation Example 1 is that no carbon black is added to material B. Example

[0048] Embodiment 1: A flexible low temperature resistant and fireproof cable, such as Figure 1 As shown, it includes multiple cable cores 1, and in this embodiment, four are taken as an example. Each cable core 1 includes multiple conductors 11 twisted with each other. In this embodiment, four are taken as an example. The conductor 11 is a tinned annealed copper wire with a diameter of 0.3 mm. The four copper conductors 11 are sequentially coated with a filling layer 14, a polytetrafluoroethylene layer 12 and an insulating reinforcement layer 13.

[0049] The filling layer 14 is formed by twisting and weaving glass fiber ropes and ceramic silicone strips in a mass ratio of 1:1. The polytetrafluoroethylene layer 12 is a polytetrafluoroethylene microporous membrane, which is selected from Shanghai Minglie New Materials, with a pore size of 0.45μm, a thickness of 20μm, and a model of X400. The insulation reinforcement layer 13 is a radiation cross-linked polyolefin cable material, which is selected from Shanghai Zhizhengdao Polymer Materials, with a model of MV-2000F.

[0050] The four cable cores 1 are sequentially coated with a heat-insulating and fire-proof layer 6, a fire-resistant and insulating layer 2, a braided copper mesh metal shielding layer 3, a polyimide outer insulating layer 4 and a PEEK insulating sheath layer 5. The heat-insulating and fire-proof layer 6 is a polyolefin material containing a flame retardant. The polyolefin material containing a flame retardant is made of the following raw materials through mixing, extrusion and granulation: 2kg of flame retardant, 2kg of PE, 4kg of EVA and 1kg of POE prepared in Preparation Example 11, PE is selected from Dow Chemical of the United States with a brand number of 3364, EVA is selected from Mitsui Chemicals of Japan with a model number of 40W, and POE is selected from Dow Chemical of the United States with a model number of 8150.

[0051] The fire-resistant insulation layer 2 is a mica tape, which is impregnated with an impregnation liquid containing a flame retardant by vacuum pressure. The vacuum impregnation pressure is -0.08MPa, the impregnation temperature is 40°C, and the time is 25min. After impregnation, the mica tape is taken out and dried at 70°C. The formula of the impregnation liquid containing a flame retardant is: 1.4kg of the flame retardant prepared in Preparation Example 11, 1.8kg of epoxy resin emulsion, 0.1kg of diethyltoluenediamine and 0.6kg of liquid polysulfide rubber. The epoxy resin emulsion is selected from Guangdong Shanghe New Materials, model WEP-6858, and the liquid polysulfide rubber is selected from Wuhan Adama New Energy, model JLY-21.

[0052] The polyimide outer insulating layer 4 is a polyimide film, and the PEEK insulating sheath layer 5 is formed by extruding a PEEK insulating sheath material, which is made by Preparation Example 1.

[0053] The method for preparing the above-mentioned flexible low-temperature resistant, fire-resistant and fireproof cable comprises the following steps: Four tinned annealed copper wires with a diameter of 0.3 mm are twisted together, and then glass fiber ropes and ceramic silicone strips are twisted and woven on four copper conductors to form a filling layer 14. Then, a polytetrafluoroethylene microporous membrane is wrapped around the outside of the filling layer 14 to form a polytetrafluoroethylene insulation layer 12. Then, a radiation cross-linked polyolefin cable material is extruded on the surface of the polytetrafluoroethylene insulation layer 12 to obtain an insulation reinforcement layer 13. The extrusion temperature of the radiation cross-linked polyethylene cable material is: 110° C. in the feeding section, 125° C. in the conveying section, 135° C. in the melting section, and 140° C. in the die head, thereby obtaining a cable core 1. The four cable cores 1 are twisted together, and then a polyolefin material containing a flame retardant is extruded outside the cable core 1. During extrusion, the temperature of the feeding section is 135°C, the temperature of the melting section is 165°C, the temperature of the homogenizing section is 175°C, and the temperature of the machine head is 170°C to form a heat-insulating and fire-proof layer 6. A mica tape is wrapped, and the mica tape is impregnated with an impregnation liquid containing a flame retardant through vacuum pressure to obtain a fire-resistant and heat-insulating layer 2. Subsequently, a braided copper mesh is wrapped on the fire-resistant and heat-insulating layer 2 to form a braided copper mesh metal shielding protective layer 3. Subsequently, a polyimide film is wrapped to form a polyimide outer insulating layer 4. Finally, a PEEK insulating sheath layer 5 is extruded on the polyimide outer insulating layer 4. During extrusion of the PEEK insulating sheath material, the temperature of the heating section is 280°C, the temperature of the melting section is 300°C, the temperature of the homogenizing section is 330°C, and the temperature of the machine head is 320°C.

[0054] Example 2: A flexible low-temperature resistant, fire-resistant and fireproof cable. The difference from Example 1 is that the PEEK insulating sheath material is made from Preparation Example 2, and the flame retardant contained in the thermal insulation and fireproof layer 6 and the fire-resistant insulation layer 2 are both made from Preparation Example 12.

[0055] Example 3: A flexible low-temperature-resistant, fire-resistant and fire-proof cable. The difference from Example 1 is that the PEEK insulating sheath material is made from Preparation Example 7.

[0056] Example 4: A flexible low-temperature-resistant, fire-resistant and fire-proof cable. The difference from Example 1 is that the PEEK insulating sheath material is made from Preparation Example 8.

[0057] Example 5: A flexible low-temperature-resistant, fire-resistant and fire-proof cable. The difference from Example 3 is that the PEEK insulating sheath material is made from Preparation Example 9.

[0058] Example 6: A flexible low-temperature resistant, fire-resistant and fire-proof cable. The difference from Example 3 is that the PEEK insulating sheath material is made from Preparation Example 10.

[0059] Example 7: A flexible low-temperature-resistant, fire-resistant and fireproof cable. The difference from Example 1 is that the flame retardant in the impregnating liquid in the thermal insulation and fireproof layer 6 is made from Preparation Example 13, and the flame retardant in the polyolefin material containing the flame retardant in the fire-resistant insulation layer 2 is made from Preparation Example 13.

[0060] Example 8: A flexible low-temperature-resistant, fire-resistant and fireproof cable. The difference from Example 1 is that the flame retardant in the impregnating liquid in the thermal insulation and fireproof layer 6 is made from Preparation Example 14, and the flame retardant in the polyolefin material containing the flame retardant in the fire-resistant insulation layer 2 is made from Preparation Example 14.

[0061] Example 9: A flexible low-temperature-resistant, fire-resistant and fireproof cable. The difference from Example 1 is that the polyolefin material containing a flame retardant in the fire-resistant insulation layer 6 is magnesium hydroxide, and the flame retardant in the impregnating liquid in the insulation and fireproof layer 2 is magnesium hydroxide.

[0062] Example 10: A flexible low-temperature resistant, fire-resistant and fireproof cable. The difference from Example 1 is that the polyolefin material containing flame retardant in the fire-resistant insulation layer 6 is selected from a commercially available product, Yancheng Ruilong Plastic Industry, model 6501-A, and the mica tape in the insulation and fireproof layer 2 has not been treated with impregnation liquid.

[0063] Comparative Example Comparative Example 1: A flexible low-temperature resistant, fire-resistant and fire-proof cable. The difference from Example 1 is that the PEEK insulating sheath material is made from Preparation Example 3.

[0064] Comparative Example 2: A flexible low-temperature-resistant, fire-resistant and fire-proof cable, which differs from Example 1 in that the PEEK insulating sheath material is made from Preparation Example 4.

[0065] Comparative Example 3: A flexible low-temperature resistant, fire-resistant and fire-proof cable, which is different from Example 1 in that the PEEK insulating sheath material is made from Preparation Example 5.

[0066] Comparative Example 4: A flexible low-temperature resistant, fire-resistant and fireproof cable, which differs from Example 1 in that the PEEK insulating sheath material is made from Preparation Example 6.

[0067] Comparative Example 5: A flexible low-temperature-resistant, fire-resistant and fire-proof cable. The difference from Example 1 is that an equal amount of ceramic silicone rubber cable material is used to replace the PEEK insulation sheath material. The ceramic silicone rubber cable material is selected from Shenzhen Longlifeng Materials, model TC90-7U.

[0068] Comparative Example 6: A ceramic silicone rubber insulated heat-resistant and fire-resistant cable, comprising a cable core and a ceramic silicone rubber insulating sheath; the raw materials of the ceramic silicone rubber insulating sheath include, by weight: 30 parts of ceramic silicone rubber, 70 parts of EPDM rubber, 10 parts of modified lignin, 20 parts of sintered red mud, 15 parts of fly ash, 16 parts of glass beads, 0.8 parts of zinc oxide, 1 part of cyclohexanone peroxide, 0.3 parts of tert-butyl perbenzoate, 1.2 parts of tert-butylphenol formaldehyde resin, 1.5 parts of diisopropyl peroxide, 3 parts of triethyl citrate, 1.5 parts of dioctyl terephthalate, 3 parts of epoxy soybean oil, 0.5 parts of tricresyl phosphate, 3.5 parts of antioxidant NBC, and 1 part of antioxidant AW.

[0069] Performance testing Cables were prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 1.

[0070] 1. Tensile strength and elongation at break: Tested in accordance with GB / T528-1998 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".

[0071] 2. Low-temperature impact brittleness temperature: Test in accordance with GB / T5470-2008 "Determination of brittleness temperature of plastics by impact method".

[0072] 3. Oxygen index: Test in accordance with GB / T2406.2-2009 "Oxygen Index Method for Testing the Combustion Performance of Wire and Cable Sheathing".

[0073] 4. Cable bundle combustion carbonization test: The test shall be carried out in accordance with GB / T18380-2008 "Combustion test of electrical cables and optical cables under flame conditions".

[0074] 5. Bending radius: Test in accordance with JB / T10696.3-2008 "Test methods for mechanical and physical and chemical properties of wires and cables Part 3: Bending test".

[0075] Table 1 Performance test results of flexible low temperature resistant and fire resistant cables Combining the data in Table 1 with the contents of Examples 1 and 2, it can be seen that the PEEK insulating sheath material prepared by Preparation Example 1 and Preparation Example 2 of the PEEK insulating sheath material, and using the thermal insulation and fireproof layer 6 and the fire-resistant insulating layer 2 containing a specific flame retardant, the cable obtained has strong tensile strength and elongation at break, low-temperature impact embrittlement performance is lower than -40°C, and has a high oxygen index, a small carbonization height, strong flame retardancy, a bending radius less than 6 times the outer diameter of the cable, is easy to move and lay, has good flexibility, and is not easy to become brittle or crack at low temperatures.

[0076] In Example 3 and Example 4, the PEEK insulating sheath materials prepared in Preparation Example 7 and Preparation Example 8 were used. Compared with Preparation Example 1, silanized cellulose nanocrystals were used to prepare polyethersulfone porous fibers. The low-temperature impact embrittlement temperature of the cable prepared in this way was further reduced, the low-temperature resistance was improved, and the mechanical strength such as tensile strength was increased, the carbonization height was reduced, the oxygen index was increased, and the flame retardant properties were improved.

[0077] In Example 5, the PEEK insulating sheath material prepared in Preparation Example 9 was used. Compared with Preparation Example 7 in Example 3, no red mud was added when preparing the polyethersulfone porous fiber. The tensile strength of the cable decreased, and the low-temperature impact embrittlement temperature did not change much, but the oxygen index decreased and the flame retardant ability decreased.

[0078] Example 6 Compared with Example 3, the PEEK insulating sheath material prepared in Preparation Example 10 was used, wherein methyltrimethoxysilane was not used to pretreat the cellulose nanocrystals. It can be seen from the data in Table 1 that the mechanical properties such as the tensile strength of the cable decreased, the brittle temperature increased, and the oxygen index and the carbonization temperature did not change much.

[0079] Compared with Example 1, Example 7 uses the flame retardant prepared in Preparation Example 13 in the fire-resistant insulation layer 6 and the thermal insulation and fireproof layer 2. Compared with Preparation Example 11 in Example 1, Preparation Example 13 has a reduced oxygen index and an increased carbonization height, while the other properties do not change much.

[0080] In Example 8, the flame retardant prepared in Preparation Example 14 was used. Compared with Preparation Example 11, the oxygen index of the cable prepared in Example 8 decreased and the flame retardant performance decreased, indicating that the flame retardant prepared in Preparation Example 11 can effectively improve the flame retardant and fireproof effects of the cable.

[0081] In Example 9, magnesium hydroxide is used as a flame retardant in the fire-resistant insulation layer 6 and the heat-insulating fireproof layer 2. Compared with Example 1, the fire resistance and fireproof effects of the cable prepared in Example 9 are worse, indicating that the flame retardant prepared in this application has better fireproof and flame-retardant effects.

[0082] In Example 10, the polyolefin material containing flame retardant in the fire-resistant insulation layer 6 is a commercially available material, and the thermal insulation and fireproof layer 2 only uses mica tape. Compared with Example 1, the other properties of the cable do not change much, but the oxygen index and carbonization height change significantly, indicating that the flame retardant of the present application can effectively improve the fire prevention and fire resistance of the cable.

[0083] Comparative Example 1 is compared with Example 1. The PEEK insulating sheath material prepared in Preparation Example 3 is used. Compared with Preparation Example 1, the carbon fiber and the polyethersulfone porous fiber are not treated with the phenylethynyl polyimide impregnation solution. Table 1 shows that the tensile strength and elongation at break of the cable prepared in Comparative Example 1 are reduced, the brittle temperature is increased, and the cold resistance is weakened.

[0084] In Comparative Example 2, the PEEK insulating sheath material prepared in Preparation Example 4 is used. Compared with Preparation Example 1, no polyethersulfone porous fiber is added. Compared with Example 1, the mechanical properties of the cable prepared in Comparative Example 2 are significantly reduced, and the brittle temperature is increased, the cold resistance is deteriorated, the bending radius is increased, and the flexibility is weakened.

[0085] Compared with Example 1, no carbon fiber is added to the PEEK insulating sheath material in Comparative Example 3. It can be seen from the data in Table 1 that the tensile strength of the cable prepared in Comparative Example 3 decreases, the low temperature resistance is weakened, and the flame retardant performance is affected to a certain extent.

[0086] Comparative Example 4 Compared with Example 1, the PEEK insulating sheath material prepared in Preparation Example 6 was used, in which TPEE was not added. Table 1 shows that the brittle temperature of the cable prepared in Comparative Example 4 increases, the low temperature resistance decreases, and the mechanical properties such as tensile strength deteriorate.

[0087] In Comparative Example 5, ceramic silicone rubber cable material is used to replace PEEK insulating sheath material, and its tensile strength is small, and its brittleness resistance temperature is lower than that of Example 1. It can be seen that the low temperature resistance effect of ceramic silicone rubber is not as good as that of PEEK insulating sheath material in this application.

[0088] Comparative Example 6 is a cable prepared by the prior art, which has a large bending radius and a high resistance to low brittle temperature, and is not easy to use or lay at low temperatures.

[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flexible low temperature resistant, fire resistant and fireproof cable, characterized in that: The invention comprises at least one cable core (1) containing a conductor (11), wherein the outer surface of the cable core (1) is sequentially coated with a fire-resistant heat-insulating layer (2), a braided copper mesh metal shielding protective layer (3), a polyimide outer insulating layer (4) and a PEEK insulating sheath layer (5), and a heat-insulating and fire-proof layer (6) is filled between the fire-resistant heat-insulating layer (2) and the cable core. The PEEK insulating sheath layer (5) is formed by extruding a PEEK insulating sheath material, wherein the PEEK insulating sheath material comprises the following raw materials in parts by weight: 2.5-4.5 parts of PEEK, 1-2 parts of TPEE, 0.5-1.5 parts of carbon fiber, 0.1-0.15 parts of phenylethynyl polyimide, and 0.5-1.5 parts of polyethersulfone porous fiber.

2. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 1, characterized in that: The preparation method of the PEE insulating sheath material is as follows: The phenylethynyl polyimide is dissolved to obtain an impregnation solution, the carbon fiber and the polyethersulfone porous fiber are immersed in the impregnation solution for 2-3 hours at room temperature, taken out and dried to obtain the pretreated fiber; The pretreated fibers are mixed evenly with a dispersant and deionized water, filtered, sprayed with a water-based epoxy adhesive, and dried to form a gauze; PEEK and TPEE are mixed and melted to obtain a melt, which is then cast into a mold multiple times, and a gauze is laid on the cast melt between each two times. Finally, the PEEK insulating sheath material is obtained by pressing at a pressure of 0.8-1.2 MPa for 20-30 seconds and crushing.

3. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 2, characterized in that: The preparation method of the polyethersulfone porous fiber is as follows: The cellulose nanocrystals are added to deionized water to prepare a suspension with a concentration of 1-2 wt%, methyltrimethoxysilane is added, the mixture is stirred at room temperature for 3-4 hours, red mud is added, ultrasonic dispersion is performed for 15-20 minutes, the mixture is freeze-dried and then crushed to obtain a porous material powder, wherein the mass ratio of the cellulose nanocrystals, methyltrimethoxysilane and red mud is 1:0.8-1:1-2; The polyethersulfone is dried and dissolved to prepare a solution with a concentration of 28-30wt%, the porous material powder is added, ultrasonic dispersion is performed for 20-30min, the solution is filtered with a 200-mesh sieve, and the solution is allowed to stand for 10-12h for degassing to obtain a spinning solution, and wet spinning is performed to obtain polyethersulfone porous fibers, wherein the mass ratio of the porous material powder to the polyethersulfone is 1.8-2.4:

100.

4. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 1, characterized in that: Each cable core (1) comprises, from the inside to the outside, a plurality of conductors (11) twisted together, a polytetrafluoroethylene insulation layer (12) wrapped around the conductor (11), an insulation reinforcement layer (13) extruded outside the polytetrafluoroethylene insulation layer (12), and a filling layer (14) filled between the conductor (11) and the polytetrafluoroethylene insulation layer (12).

5. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 4, characterized in that: The polytetrafluoroethylene insulation layer (12) is a polytetrafluoroethylene microporous membrane.

6. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 4, characterized in that: The insulating reinforcement layer (13) is made of radiation cross-linked polyolefin cable material.

7. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 1, characterized in that: The heat-insulating and fire-proofing layer (6) is a polyolefin material containing a flame retardant.

8. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 1, characterized in that: The fire-resistant heat-insulating layer (2) is a mica tape impregnated with an impregnation liquid containing a flame retardant by vacuum pressure.

9. The flexible low temperature resistant, fire resistant and fireproof cable according to claim 7 or 8, characterized in that: The preparation method of the flame retardant is as follows: Disperse the carbon microspheres in anhydrous ethanol, add ammonia water until the pH value is ≥12, heat to 40-45°C, add magnesium chloride solution until the pH value is 10, stir at constant temperature for 1-2h, filter, wash, dry and grind to obtain material A; Mix lauric acid and tetradic acid at a molar ratio of 6:4 at 70-80°C to obtain a phase change material, add nano-silicon dioxide and carbon black, stir for 1-2 hours, and vacuum dry to obtain material B, wherein the mass ratio of the phase change material, nano-silicon dioxide and carbon black is 1:0.6-0.8:0.16-0.18; The material A and the material B are uniformly mixed in a mass ratio of 1:0.4-0.6 to prepare a flame retardant.

10. The method for preparing the flexible low temperature resistant, fire resistant and fireproof cable according to any one of claims 1 to 9, characterized in that: The following steps are involved: A plurality of conductors (11) are twisted together, and then a glass fiber rope and a ceramic silicone strip are twisted and braided on the twisted plurality of conductors (11) to form a filling layer (14), a polytetrafluoroethylene microporous membrane is wrapped outside the filling layer (14) to form a polytetrafluoroethylene insulation layer (12), and then a radiation cross-linked polyolefin cable material is extruded on the surface to obtain an insulation reinforcement layer (13), thereby obtaining a cable core (1); A polyolefin material containing a flame retardant is extruded on at least one cable core (1) to obtain a heat-insulating and fire-proof layer (6), which is then wrapped with a mica tape that has been vacuum-pressure-impregnated with an impregnation liquid containing a flame retardant to obtain a fire-resistant and heat-insulating layer (2), and then a braided copper mesh is wrapped to form a braided copper mesh metal shielding protective layer (3), followed by a polyimide film to form a polyimide outer insulation layer (4), and finally a PEEK insulation sheath layer (5) is extruded on the polyimide outer insulation layer.

Citation Information

Cited By

  • High-elongation aluminum alloy conductor reinforcing band wrapped cable

    CN120452900A

  • Fireproof alumina fiber-containing cable outer sheath material

    CN120484362A